Kepastian Hukum Implementasi Denda Damai Untuk Perkara Tindak Pidana Korupsi: Legal Certainty in the Implementation of Peaceful Fines for Corruption Crime Cases - Sianturi, Ronal Hasudungan; Tanjung, Ahmad Feri; Christian Naldo, Rony Andre (Universitas Medan Area, 2025)
This article aims to examine the legal certainty of the implementation of a peace fine against the alleged perpetrators of corruption. Peaceful fines are regulated in Law Number 20 of 2001 Concerning Amendments to Law Number 31 of 1999 Concerning Eradication of Corruption Crimes, namely in Article 35 paragraph (1) letter k. The executive had discussed the implementation of a peaceful fine against the alleged perpetrators of corruption. The discourse of implementation has caused controversy in Indonesia, so that in the end the discourse was canceled. The problem is focused on the executive discourse to implement a peaceful fine against the alleged perpetrators of corruption. The theory used in analyzing the problem approach is the theory of legal certainty put forward by C.S.T. Kansil. According to C.S.T. Kansil, normative legal certainty is when a regulation is made and promulgated with a clear and logical manner. Data are collected through primary legal materials, secondary legal materials, as well as tertiary legal materials, and are analyzed qualitatively. This study concluded that the implementation of peaceful fines against alleged perpetrators of corruption is inappropriate, contrary to Law Number 20 of 2001 Concerning Amendments to Law Number 31 of 1999 Concerning Eradication of Corruption and Law Number 11 Year 2021 Concerning the Prosecutor's Office of the Republic of Indonesia, as well as causing legal uncertainty in law enforcement.